Variation in Benthic Macroinvertebrates Along aLongitudinal Gradient of a Disturbed Nyakambu Stream Kabale District Southwestern Uganda. - Byaruhanga, Benson (Kabale University, 2024)
Anthropogenic disturbances in streams are occasioned by the necessity for social amenities by man and vary from region to region. In the tropics the demands for domestic water are common (Mathooko et al. 2009), which become detrimental to the associated water resources when they exceed the tolerance range of the macroinvertebrate community and also affect individual taxa composition, thus impacting stream ecosystem functioning (Meyer 1997; Wagenhoff et al. 2011). The study assessed the impact of human activities on water quality and macroinvertebrate assemblages. It also assessed the response of macroinvertebrate-based indices of water quality to pollution levels. Macroinvertebrate community and physico-chemical variables data were collected from 6 sites. Two sites downstream were compared with 2 sites in the middle stream and two sites upstream. Of the downstream sites, 13 were situated at low altitudes. An increase in temperature, increase in conductivity, and total dissolved solids was observed in downstream sites. Macroinvertebrate community structure and South African Scoring System (SASS) scores closely followed the induced changes in water quality due to human activities. However, water quality variables, macroinvertebrate community structure, and SASS scores reverted back as some tolerant families and high turbidity and conductivity were recorded from the midstream sites. Tolerant families were recorded both in the down and midstream and sensitive species were collected in the upstream such as plecopterans and trichopterans following the EPT concept. Low temperatures and high pH were recorded in the upstream due to the abundance of undisturbed vegetation and less impact of human activities on the stream. Low pH was recorded in the downstream sites due to urbanization, which leads to increased pollution levels through poor disposal of sewage and other wastes.